Understanding Related to Early Marriage Counseling to PKK Mothers in Petiken Village, Driyorejo District, Gresik Regency - Kusumah, Fiona Restu; Ussafina, Luluk; Quraini, Annisa; khusnah, Dea April Haniatul; Nugraha, imas Nurzullah Eka; Khasanah, Rohmatul (UNUSA Press, 2023)
The people of Petiken Village, Driyorejo District, Gresik Regency have a tendency to marry underage. This is based on the results of research conducted in 2022. Marriage that is carried out at an early age will cause problems both from health, legal and educational aspects. The purpose of implementing this community service activity is to provide information and increase the knowledge of the people of Petiken Village due to early marriage from the aspects of health, law and family education. The community service activities carried out are in the form of identification of local wisdom of the community, identification of village community resources, counseling related to early marriage including legal aspects, reproductive health, adolescent health and indirect impacts of early marriage. The result of the counseling provided is that all PKK administrators agree and support all efforts that can reduce the incidence of early marriage in the Petiken village area by forwarding the results of this counseling to early childhood children and their parents that marriage should be carried out when a person is mentally and socially and physically ready. This will have a positive impact on the new generation of quality.